Effects of the Affordable Care Act on part-time employment: Early evidence - Marcus Dillender; Carolyn J. Heinrich; Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2016)
The Affordable Care Act (ACA) requires employers with at least 50 full-time-equivalent employees to offer "affordable" health insurance to employees working 30 or more hours per week. If employers do not comply with the mandate, they may face substantial financial penalties. Employers can potentially circumvent the mandate by reducing weekly hours below the 30-hour threshold or by using other nonstandard employment arrangements (direct-hire temporaries, agency temporaries, small contractors, and independent contractors). We examine the effects of the ACA on short-hours, part-time employment. Using monthly CPS data, we estimate that the ACA resulted in an increase in low-hours, involuntary part-time employment of a half-million to a million workers in retail, accommodations, and food services, the sectors in which employers are most likely to reduce hours if they choose to circumvent the mandate, and also the sectors in which low-wage workers are most likely to be affected. Our empirical strategy uses as a control group Hawaii, which has had a more stringent employer health insurance mandate than that of the ACA for several decades. The findings are robust to placebo tests and alternative specifications.
Keywords: I13; J23; J3; 330; Affordable Care Act; employer-sponsored health insurance; employer mandate; part-time employment; involuntary part-time employment